Factors Affecting Student Learning Achievement in Asian Universities During the Pandemic Period - Jennifer, Nelson; William, Bumgarner; Richmond, Hecmarie; James, Randy; DeVries, Simpkins (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2022)
Students in universities during the pandemic tend to carry out the learning process not face-to-face, but only carry out the learning process online or often called online learning such as students in universities learning through the Zoom application, Google Meet, giving and collecting assignments via WhatsApp, Gmail, Google Classroom and e-Campus. During this pandemic, the learning process has become less effective. This affects student learning achievement in higher education. The purpose of this study was to determine the factors that affect student learning achievement in higher education during the pandemic. This research uses a quantitative method using a survey model. The survey tool that researchers use is Google Form. The results of this study indicate that student learning achievement has decreased during the pandemic because the teaching and learning process is not running effectively. The conclusion of this study explains that lecturers have a very important role in overcoming the factors that affect student learning achievement. The role of lecturers is to be able to motivate students to be more diligent and active in learning, lecturers can provide guidance to students whose learning achievement has decreased so that student achievement increases. Therefore, the limitation of this study is that researchers only conduct research on factors that affect student learning achievement in higher education, researchers hope to conduct research in other universities.